PERCEIVED LEARNING OUTCOMES AND TEAM BEHAVIOR IN ENTREPRENEURIAL VENTURE CREATION UNIVERSITAS CIPUTRA SURABAYA 2020 - Yuanita Ratna Indudewi (FIRM Journal of Management Studies, 2021)
Entrepreneurial Venture Creation is one of signature curricula in International Business Management Universitas Ciputra Surabaya. It is part of 7 semesters Entrepreneurship Education Journey to equip students with entrepreneurial skill by doing real business project.  It is a set skill that helps students to face volatile, uncertain, complex and ambiguous (VUCA) future. Especially during COVID-19, it’s one of a real case study of VUCA. During Entrepreneurial Venture Creation (EVC), students guided through design thinking phase starting from empathize, defining problem, ideation and prototyping, market testing, finally they evaluate and conclude their venture development. Half of the design thinking process of EVC was done remotely in an online classroom platform due to COVID-19. The purpose of this research is to evaluate whether Entrepreneurship Education intervention in form of Entrepreneurial Venture Creation curricula can increase their perceived knowledge, perceived entrepreneurial mindset, and perceived venture creation skill. This study also want get a closer understanding how team behavior can interfere their venture continuation. There are 533 of second semester students who were participated in the survey. Total population sampling was used in the process. The result of simple statistic descriptive showed they have positively increased their perceived entrepreneurial knowledge, perceived entrepreneurial mindset and perceived venture creation skill, whether they have a good team behavior or not. The statistic showed that there are 9.19% teams that didn’t have good behavior and decided to discontinue their venture, yet still have high perceived entrepreneurial knowledge, perceived entrepreneurial mindset, and perceived venture creation skill.